2015
DOI: 10.1155/2015/987048
|View full text |Cite
|
Sign up to set email alerts
|

Fusional Vergence Detected by Prism Bar and Synoptophore in Chinese Childhood Intermittent Exotropia

Abstract: Purpose. To measure the changes in fusional vergence in Chinese children with intermittent exotropia (IXT) and the association with the control of IXT. Methods. Ninety-two patients with IXT (8–15 years old) were compared with 86 controls. Exodeviation control was evaluated using the Revised Newcastle Control Score. Angle of deviation was measured using prism and alternate cover testing at distance and near. Fusional vergence was measured using prism bar and synoptophore. This study was registered with ChiCTR-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 20 publications
2
22
1
1
Order By: Relevance
“…Stereoacuity was recorded as "nil" if patients could not pass the largest disparity. Fusional convergence was detected via a synoptophore with fusion slides [22]. Patients were first instructed to move the tube to create a composite image (i.e., simultaneous perception).…”
Section: Data Collectionmentioning
confidence: 99%
“…Stereoacuity was recorded as "nil" if patients could not pass the largest disparity. Fusional convergence was detected via a synoptophore with fusion slides [22]. Patients were first instructed to move the tube to create a composite image (i.e., simultaneous perception).…”
Section: Data Collectionmentioning
confidence: 99%
“…When analyzing the existing relationships, considering the normative values of both the variables that defined the binocular vision status and the variables referring to the state of the cervical region, we found that in subjects with a smaller amplitude of PFV near, a situation that is identified with insufficiency of convergence [38,41–43], a higher percentage presented altered AS values (below 4 points). Similarly, in the group of subjects who did not comply with Sheard's criterion (near), a situation that is identified with unstable binocular vision, there was a higher percentage of individuals with decreased AS values In the same way, among the subjects who had NFV (distance) break above the norm (excess of divergence) [36,37,45] and subjects who had PFV (near) blur values below the norm (insufficiency of convergence) [38,41–43], we found a higher percentage with decreased levels of AS (below 4). On the other hand, in subjects with decreased vergence facility (near) (fusional vergence dysfunction) [30,46], a greater percentage reported cervical pain of three or more months of evolution and therefore a tendency to suffer cervicalgia compared to subjects in whom the value of vergence facility (near) was normal; among the latter, a lower number reported pain.…”
Section: Discussionmentioning
confidence: 97%
“…We identified subjects who presented values of NFV (distance) break above the norm, a condition that causes a tendency toward greater amplitudes of divergence and is associated with greater exodeviation in far than in near, signs that characterize an excess of divergence [36,37]. This group presented low AS and PI compared to the group whose NFV (distance) break value was normal (Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…Bei Patienten, die den Test bei der größten Disparität nicht bestanden, wurde die Stereosehschärfe als «Null» eingestuft. Die fusionale Konvergenz wurde mit einem Synoptophor und Fusionsprüfbildern nachgewiesen [22]. Die Patienten wurden zunächst gebeten, die Röhre so einzustellen, dass ein Summenbild entstand (d.h. Simultansehen).…”
Section: Methodeunclassified